MITO: A new operational model for the forecasting of the Mediterranean sea circulation - Napolitano, E.; Iacono, R.; Palma, M.; Sannino, G.; Carillo, A.; Lombardi, E.; Pisacane, G.; Struglia, M. V. (Frontiers in Energy Research, 2022)
Availability of detailed short-term forecasts of the ocean circulation and of the sea state (waves) is essential for a correct management of human activities insisting on coastal areas. Together with marine transportation, fishing, aquaculture, coastal management, and save and rescue, such activities include the extraction of renewable energy, which has strongly developed in recent years, and will play a key role in the context of future blue growth. The present work is concerned with the description and validation of a new operational model for the forecasting of the Mediterranean Sea circulation, which includes the main effects of tidal forcing, both local and propagating from the Atlantic. Since 2018, this model, named MITO, has been providing daily five-days forecasts of the Mediterranean Sea circulation. A distinctive feature of the model is the high horizontal resolution, which is of 1/48° (about 2 km) in most of the computational domain, but is smoothly increased (down to few hundred meters) in key passages, such has the Gibraltar Strait and the Turkish Straits, to correctly resolve the complex local dynamics. A thorough validation of the model has been performed, analyzing the forecasts of the year 2020, whose results were compared with the available in situ and remote experimental data (sea surface temperature, altimeter data, temperature and salinity profiles by floats, tide-gauge measurements), using the same large-scale metrics applied in the validation of the Copernicus operational model. The comparison shows that MITO results are generally in very good agreement with the observations, despite the fact that the model does not make explicit use of data assimilation. Examples will also be given of the capability of the model to correctly describe complex local mesoscale dynamics. Finally, a few aspects that need improvement will be noted, which will be addressed in a future upgrade of the operational implementation.